2011
DOI: 10.1021/la200381f
|View full text |Cite
|
Sign up to set email alerts
|

Methylated β-Cyclodextrins: Influence of Degree and Pattern of Substitution on the Thermodynamics of Complexation with Tauro- and Glyco-Conjugated Bile Salts

Abstract: The complexation of 6 bile salts with various methylated β-cyclodextrins was studied to elucidate how the degree and pattern of substitution affects the binding. The structures of the CDs were determined by mass spectrometry and NMR techniques, and the structures of the inclusion complexes were characterized from the complexation-induced shifts of (13)C nuclei as well as by 2D ROESY NMR. Thermodynamic data were generated using isothermal titration calorimetry. The structure-properties analysis showed that meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
88
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(100 citation statements)
references
References 46 publications
12
88
0
Order By: Relevance
“…39 We have studied CDs with five substituents (HP060) and seven substituents (HP100). HP substituents were placed on O2, O3, and O6.…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…39 We have studied CDs with five substituents (HP060) and seven substituents (HP100). HP substituents were placed on O2, O3, and O6.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…5,36 Empirically, an enthalpy−entropy compensation has been observed in a large variety of CD inclusion complexes, 17,37,38 including complexation of glycoconjugated bile salts (BSs) with β-CD and β-CD decorated with HP substituents. 39 In these studies, it has been found that TΔS°and ΔH°upon complexation between HP-substituted β-CD and BSs increase with increased degree of substitution (DS). It has been estimated that this is caused by the increase in dehydration of the hydrophobic surface area as a consequence of increased DS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of substitution and its effect on the stability constant for complexes with modified βCDs has previously been investigated in several studies and shown to be highly influenced by the guest molecule (e.g. Schönbeck et al, 2010Schönbeck et al, , 2011Yuan et al, 2008; Buvári-Barcza and Barcza, 1999). The substituents on the CDs are in general considered to extent the cavity, which increases the hydrophobic interactions between the hydrophobic part of the small guest molecule protruding the cavity and the substituent causing a stronger binding (Yuan et al, 2008;Buvári-Barcza and Barcza, 1999).…”
Section: Complexation Constantsmentioning
confidence: 99%
“…Among the numerous guests researched, bile salts attracted much more attention because they are one kind of important surfactant-like biological amphipathic compounds possessing a steroid skeleton, which have distinctive detergent properties and play an important role in the metabolism and excretion of cholesterol in mammals [6]. For example: the thermodynamics and structure of inclusion compounds of glyco-and tauro-conjugated bile salts with CDs and their derivatives have been studied by Holm et al during the last years [7][8][9][10][11]; the interactions of different kinds of bile salts with -CD dimers linked through their secondary faces have been investigated by Reinhoudt and Vargas-Berenguel et al [12][13][14]. It has been demonstrated that the formation of inclusion complexes between CDs and guest molecules is cooperatively governed by several weak forces, such as van der Waals interactions, hydrophobic interactions, hydrogen bonding, electrostatic interactions, and every weak force does its contribution to the complexation.…”
Section: Introductionmentioning
confidence: 99%